Scoping visit to identify potential study sites for Taenia solium research in northern Uganda - Ngwili, Nicholas M.; Ahimbisibwe, Salaviriuse; Thomas, Lian F.; Sentamu, Derrick (International Livestock Research Institute, 2022)
Taenia solium (pork tapeworm) is a key neglected zoonotic parasite that causes serious public health and socio-economic problems in the global south. T. solium infection results in three different illnesses: Porcine cysticercosis in pigs and Taeniasis and Neurocysticercosis in humans. Neurocysticercosis is the leading cause of preventable adult-acquired epilepsy in sub-Saharan countries, including Uganda. Although its control is not considered a key priority, T. solium infections have been listed among zoonotic diseases present in Uganda by the national One Health platform (Sekamatte et al., 2018). In Uganda, the endemicity of T. solium is aided by high household poverty rates, low coverage and use of appropriate sanitary infrastructure, rudimentary extensive pig production systems (free-roaming pig keeping), and poor public health systems.